Brief Report: Virtual Reality to Raise Awareness About Autism. - Koniou, Ioulia; Douard, Elise; Lanovaz, Marc J. (Journal of Autism & Developmental Disorders, 2025)
Purpose: The purpose of the study was to develop and test a virtual reality application designed to put the participants "in the shoes" of an autistic person during a routine task. Method: The study involved a randomized controlled trial that included 103 participants recruited from a technical college. Each participant responded to three questionnaires to measure attitudes, knowledge, and openness toward autism. Prior to responding to these questionnaires, the participants in the experimental group also completed an 8-min virtual reality simulation designed by the research team in collaboration with autistic individuals. Results: The participants who completed the virtual reality simulation reported better attitudes, more knowledge, and higher openness toward autism than the participants in the control group. Conclusion: The results of the study suggest that virtual reality simulations are promising tools to raise awareness about autism.